The standard form is:
![y=ax^2+bx+c](https://img.qammunity.org/2023/formulas/mathematics/high-school/g7mvpjunjwe6qob7ddy7l4f0glbtdi9gci.png)
To get it from the vertex form we need to do the operations and simplify like terms. With this in mind we have:
a.
![\begin{gathered} y=(x+5)^2+4 \\ y=x^2+10x+25+4 \\ y=x^2+10x+29 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yrlp9o1981clv6xes12e43xj67n9msxv2h.png)
Therefore the standard form is:
![y=x^2+10x+29](https://img.qammunity.org/2023/formulas/mathematics/college/tcfbbn16hb2nyx1cl51jok1cz67ijfmv0n.png)
b.
![\begin{gathered} y=2(x-7)^2-8 \\ y=2(x^2-14x+49)-8 \\ y=2x^2-28x+98-8 \\ y=2x^2-28x+90 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6702yzph2wojb2ebmqfr7z6ohqby29r5eg.png)
Therefore the standard form is:
![y=2x^2-28x+90](https://img.qammunity.org/2023/formulas/mathematics/college/9ghh6s9yp262o2tys61jctqbu1drfyfymc.png)
c.
![\begin{gathered} y=-3(x+4)^2+1 \\ y=-3(x^2+8x+16)+1 \\ y=-3x^2-24x-48+1 \\ y=-3x^2-24x-47 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9wlz5xz6o7s4zz061ngr6612dcf381kl9v.png)
Therefore the standard form is:
![y=-3x^2-24x-47](https://img.qammunity.org/2023/formulas/mathematics/college/i572wmu4b2z90n2cyty96iot625l8lmbxe.png)
d.
![\begin{gathered} y=0.5(x-3)^2-4.5 \\ y=0.5(x^2-6x+9)-4.5 \\ y=0.5x^2-3x+4.5-4.5 \\ y=0.5x^2-3x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tj94e8w2bp31711ldmytlt3849i6vhlalr.png)
Therefore the standard form is:
![y=0.5x^2-3x](https://img.qammunity.org/2023/formulas/mathematics/college/38suc1uxv1saeuohjaartkl2djs2tcz81k.png)